Effects of audiovisual interactions on working memory: Use of the combined N-back + Go/NoGo paradigm - He, Yang; Yang, Tianqi; He, Chunyan; Sun, Kewei; Guo, Yaning; Wang, Xiuchao; Bai, Lifeng; Xue, Ting; Xu, Tao; Guo, Qingjun; Liao, Yang; Liu, Xufeng; et al. (Frontiers in Psychology, 2023)
Abstract Background: Approximately 94% of sensory information acquired by humans originates from the visual and auditory channels. Such information can be temporarily stored and processed in working memory, but this system has limited capacity. Working memory plays an important role in higher cognitive functions and is controlled by central executive function. Therefore, elucidating the influence of the central executive function on information processing in working memory, such as in audiovisual integration, is of great scientific and practical importance. Purpose: This study used a paradigm that combined N-back and Go/NoGo tasks, using simple Arabic numerals as stimuli, to investigate the effects of cognitive load (modulated by varying the magnitude of N) and audiovisual integration on the central executive function of working memory as well as their interaction. Methods: Sixty college students aged 17-21 years were enrolled and performed both unimodal and bimodal tasks to evaluate the central executive function of working memory. The order of the three cognitive tasks was pseudorandomized, and a Latin square design was used to account for order effects. Finally, working memory performance, i.e., reaction time and accuracy, was compared between unimodal and bimodal tasks with paired-sample t test. Results: As cognitive load increased, the presence of auditory stimuli interfered with visual working memory by a moderate to large extent; similarly, as cognitive load increased, the presence of visual stimuli interfered with auditory working memory by a moderate to large effect size. Conclusion: Our study supports the theory of competing resources, i.e., that visual and auditory information interfere with each other and that the magnitude of this interference is primarily related to cognitive load.